Cutaneous schwannoma presenting as a lower back mass. (2017) - Patel, Hunaiz A.; Makhijani, Sumeet
Highlights: Schwannomas are benign neoplasms composed of Schwann cells, that can arise anywhere in the body. Schwannomas arise mainly in the dermal and subcutaneous tissue layers. In this case report, we present a cutaneous schwannoma presenting as an enlarging left lower back solitary mass that was surgically excised.